2022
DOI: 10.3390/polym14091839
|View full text |Cite
|
Sign up to set email alerts
|

Graphene Oxide Molecularly Imprinted Polymers as Novel Adsorbents for Solid-Phase Microextraction for Selective Determination of Norfloxacin in the Marine Environment

Abstract: In this study, a novel sample pretreatment strategy of solid-phase microextraction using graphene oxide molecularly imprinted polymers as adsorbents coupled with high-performance liquid chromatography was developed to detect norfloxacin in the marine environment. As a carrier, the imprinted polymers were synthesized by precipitation polymerization with graphene oxide. Compared with graphene oxide non-imprinted polymers, the graphene oxide molecularly imprinted polymers exhibited higher adsorption capacity towa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 48 publications
0
6
0
Order By: Relevance
“…However, GO and rGO are toxic, damaging to cells and polluting the environment, so GO and rGO should be used appropriately. Chen et al 75 used GO MIPs as adsorbents to detect NOR in the marine environment by solid-phase microextraction combined with high performance liquid chromatography. The method was then applied to analyze NOR in seawater and sh with the recoveries of 90.1-102.7%.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, GO and rGO are toxic, damaging to cells and polluting the environment, so GO and rGO should be used appropriately. Chen et al 75 used GO MIPs as adsorbents to detect NOR in the marine environment by solid-phase microextraction combined with high performance liquid chromatography. The method was then applied to analyze NOR in seawater and sh with the recoveries of 90.1-102.7%.…”
Section: Methodsmentioning
confidence: 99%
“…Chen et al 75 used GO MIPs as adsorbents to detect NOR in the marine environment by solid-phase microextraction combined with high performance liquid chromatography. The method was then applied to analyze NOR in seawater and fish with the recoveries of 90.1–102.7%.…”
Section: Application Of Mit Based On Functional Nanoparticles In the ...mentioning
confidence: 99%
“…However, after 60 min, the increase in adsorption efficiency began to decrease. After 60 min, it was discovered that the increments were negligibly small as the system approached equilibrium [56]. It has been reported that polymeric adsorbent composites have a very fast equilibrium compared to other adsorbents, which can take several days to reach equilibrium [57].…”
Section: Effect Of Contact Timementioning
confidence: 99%
“…[28][29][30][31][32] Recently, a novel SPME sample pretreatment strategy was developed for the detection of norfloxacin in the marine environment by preparing graphene oxide molecularly imprinted polymers and then loading the polymers onto molecularly imprinted solid phase microextraction columns. 33 In addition, MIP-SPME is highly sensitive and convenient for the selective and high-throughput determination of various organophosphate flame retardants at trace levels in environmental matrices. 25 However, MIP-SPME is typically prepared using a single template, thus resulting in the selective recognition of only pre-concentrated single or a group of structurally analogous compounds.…”
Section: Introductionmentioning
confidence: 99%